Under a $50/ton carbon tax, US emissions would decline 15-20% by 2030. - Barthes (Isonomia, 2025)
Under a $50/ton carbon tax, US emissions would decline 15-20% by 2030.
iso-id: iso:argument:QFkSE1IH; sha256: sha256:4793bfd20965bae9cd60fd979eb39a880c2405489c7ace873cfa22f8478ebda5